P Pengaruh Pengetahuan, Sikap Dan Perilaku Pertolongan Pertama Pada Kecelakaan Pada Siswa Sekolah Dasar di Kecamatan Medan Tuntungan: Influence of Knowledge, Attitude and Behavior of First Aid in Accidents among Elementary School Students in Medan Tuntungan Subdistrict - Napitupulu, Siska Mariany Ocfica; Nurliyati, Nurliyati (Journal of Nursing Invention, 2023)
Background: First aid can promote a safer and healthier environment. Providing education to school-age children allows them to learn faster and be more motivated than adults.Objective: The purpose of this study was to identify the effect of knowledge, attitude and behavior of first aid on elementary school students.Methods: The research design developed was descriptive quantitative. The variables in this study consisted of knowledge and attitudes taken cross sectionally, and behavior variables taken retrospectively. This study was conducted in Medan Tuntungan Subdistrict, namely at Bharlind School Elementary School based on data that the school has coverage of the implementation of first aid at the Medan Tuntungan Health Center, Medan City. The research was conducted in November 2023-January 2024. The population of this study were all V and VI grade students totaling 87 people. The sampling technique used total sampling. Instruments to measure the level of knowledge attitudes and behavior using a questionnaire.Results: The results showed that most students had good knowledge about first aid, but had a negative attitude and almost all students had poor behavior in first aid actions.Conclusion: Based on the results of the study, it is necessary to increase the knowledge of first aid in elementary school students, especially in the attitude and behavior of first aid. These activities can be carried out by optimizing the first aid program in accidents through counseling, motivation, and supervision of the implementation of first aid at school.